House or flat? - Vale, Brenda; Vale, Robert (Architectural History Aotearoa, 2022)
The modern argument of high density versus low density living is not new. In 1915 Florence Taylor wrote an article for the Australian journal Building, entitled "The Home - or the Flat?’" (Taylor "The Home - or the Flat?" pp 125-126), Before reading on, the reader knew from the article title that a house was a home and a flat was not. Taylor’s argument was that women who lived in flats would become "flaccid and unwomanly" and fail to bear children (she was childless). She believed that "cheap and convenient suburban transport [based on "State-owned trams" which made "communication … easy and cheap"] … together with wide suburban areas offers the best solution of the healthy, prolific population." By the 1920s she had changed her opinion in favour of flats. A similar process at later dates occurred in New Zealand where in 1919 Samuel Hurst Seager used the report of the 1918 town planning conference in Brisbane to promote the garden village with its separate homes as the answer to the New Zealand housing problem. However, by 1936 in the first issue of Building Today (later Home and Building) the inner city Cintra House flats in Auckland were hailed as "... a very fine practical home for modern living" (Anon "Cintra" pp 19-21). The architect was Horace Massey and much of the fitted interior furniture that gave this practicality was designed by RGS Beatson, the newly appointed co-editor of Home and Building.